A Randomised Control Trial evaluating The GUIDE Cymru: All Wales mental health literacy in Year 9 children in Wales - NICOLA SIMKISS (2023)
Adolescent and young people’s mental health problems are increasingly prevalent within the United Kingdom (UK), and a lack of mental health knowledge can often lead to negative stereotypes of mental illness. This thesis aims to contribute to the expanding field of Mental Health Literacy (MHL) among adolescents and young people. Chapter 1 outlined the prevalence of mental health problems during adolescence and the need for early intervention. Chapter 2 reviews mental health stigma and details the importance of stigma reduction through improving knowledge and MHL. Chapter 3 introduces the development of a new measure of MHL, known as the Knowledge and Attitudes to Mental Health Scale (KAMHS).Chapter 4 investigates associations between mental health and MHL constructs and assesses the importance of MHL as more than just mental health knowledge, extending to the broader construct of help-seeking efficacy, stigma, and coping mechanisms. Chapter 5 outlines a pilot study in the evaluation of the Guide Cymru through a pre and post-test design. Moreover, Chapter 6 illustrates a cluster randomised control trial used to evaluate a The Guide Cymru within secondary schools across Wales. Chapter 7 reviews the research presented throughout the thesis, considering the broader implications of the findings and recommendations for future research. This thesis, therefore, contributes to the field of MHL by demonstrating that providing teachers with appropriate resources and training to deliver the Guide Cymru can significantly improve the MHL of pupils. The findings provide valuable insights into future research supporting child and adolescent mental health.